The Quality of Governance and Economic Growth in Croatia - Marijana Bađun (Financial Theory and Practice, 2005)
The objective of this paper is to show the justification and importance of explicit inclusion of quality of governance in the debate on economic growth in Croatia. Governance is defined as the manner in which the state employs its power in handling the institutional environment, thus affecting the accumulation of economic growth factors. Although there are numerous elements in the quality of governance, this paper places the emphasis on the whole on two of them: the rule of law and the quality of the public administration. In pursuit of its objective, the paper first of all considers the links between governance and economic growth in growth theory and empirical research to date. After that an econometric (panel) analysis of quality of governance and economic growth on a sample of EU countries and Croatia, Bulgaria and Romania (EU accession candidate countries) is performed, and then changes in the quality ofgovernance in Croatia are considered. From a comparison of the values of indicators of the rule of law and quality of the public administration, and the dynamics and nature of reform in the administration of justice and the civil service, it appears that those in whom power is vested in Croatia are more focused on rent-seeking than is the case in the average of EU countries. Institutional shortcomings have affected the current level of real per capita GDP in Croatia, and more rapid and effective reforms of the justice and public administration sectors, as well as fighting corruption and boosting democracy (as mechanism for controlling those in whom power is vested) would have a positive effect on future economic growth.